Analysis of the temperature behavior model for the optimization of sowing (TOMATO (Solanum licopersicum)) (Revista Científica Interdisciplinaria Investigación y Saberes, 2021)
Mathematics has continued to increase its presence in the sciencesand in the economic sectors, in general. Along with informationtechnologies, huge volumes of data are processed that facilitateanalysis and serve for objective decision-making. The avoidance ofagricultural risks is a task of the first order to safeguard foodsecurity and thus reducing the vegetative periods in crops is aneffective strategy to achieve it. The work is carried out in theBabahoyo canton, Los Ríos province on obtaining behavior modelsof air temperatures that facilitate, through the application ofDifferential Calculation, obtaining the dates of maximumtemperatures, which would allow obtaining the periods of highertemperatures. thermal supply to accelerate growth anddevelopment processes. The dates of maximum temperature werelocated around decade 7, between March 13 and 17, results of thesum of probabilities for 75%. The sums of temperatures obtainedfluctuate in the range 2170 – 2266 Celsius Degrees that guaranteethe acceleration of the vegetative period, since they have 100% ofthe sum of probabilities of being reached. Observe a managementdirected to the selection of the period of highest temperature willreduce the risks of pests and extreme events, in addition toreducing inputs in agricultural production, which will increase thesustainability of the system.